Interactive e-learning forum web application for FICT UTAR - Chai, Wan Xin (2021)
In this digital era, advancement in computer, communication technologies and the internet enable boundless peer-to-peer interaction regardless of where the people are. Other than communication, the advancement of these technologies also slowly showing its influence in education, the universities are rapidly converting the physical studies mode into the online education. Recently, COVID-19 are causing havoc all around the world, people are practicing social distancing to prevent spreading of the infections. Education is affected adversely as well due to the COVID-19 as the students are not allowed or encouraged not to return to campus. Therefore, UTAR has conducted online learning in order to enable the students to continue learning in this pandemic. However, students are having difficulties when having their online learning session. Hence, a platform that allows discussion among students are needed urgently. Nonetheless, although most of the communication platforms are evolving in a very fast pace and show no sign of stopping, the forum of UTAR have not been changed or updated along the way. The forum of UTAR plays a little role when comes serving the purpose of letting students discuss and interact with each other. This project is a forum web application for FICT UTAR students. It will not only act as a platform for students to make discussions and solving their problems, but also improves the students’ learning experience especially in this COVID-19 pandemic, where online learning become the new normal. This project focus on interactivity of the forum because high interactivity encourages students to continue to use it throughout their university life. A back-office web application is developed to allow FICT UTAR lecturers and staffs to monitor the statistics produced using the data gathered in the forum. The development of the project is separated into front-end, which is the presentation layer and backend, the data access layer. The front-end is developed using Reactjs, a Javascript library for building user interface and UI components. On the other hand, back-end is developed using PHP, which is a general-purpose scripting language suited to web development and the database used is MongoDB. RESTful API, which use HTTP requests to access data will beused to connecting the front-end and back-end. The deliverable of this project could benefit FICT UTAR by improving the students’ learning experience and provide statistic for analyzation.